Asymptotic Study of a Boundary Value Problem Governed by the Elasticity Operator with Nonlinear Term (Advances in Applied Mathematics and Mechanics, 2014)
In this paper, a nonlinear boundary value problem in a three dimensionalthin domain with Tresca's friction law is considered. The small change of variablez = x3/ε transforms the initial problem posed in the domain Ωε into a new problemposed on a fixed domain Ω independent of the parameter ε. As a main result, weobtain some estimates independent of the small parameter. The passage to the limiton ε, permits to prove the results concerning the limit of the weak problem and itsuniqueness.